THE ROLE OF THE EDUCATION SYSTEM IN IMPROVING THE LEGAL CULTURE OF YOUTH IN UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2023)
This article talks about the place and role of the education system in shaping the legal consciousness of the population in our country, the means of ensuring the legal education of young people, as well as a number of fundamental reforms that are being carried out to further develop the legal consciousness and legal culture of the population.